GAMIFICATION IN TEACHING ENGLISH (Ustozlar uchun, 2026)
This article examines the role of gamification in teaching English as a foreign language. Gamification involves integrating game elements such as points, badges, levels, and rewards into the educational process to increase students’ motivation and engagement. The study highlights the pedagogical value of gamification in developing language skills, particularly speaking, listening, reading, and writing. It also discusses how digital tools and interactive platforms contribute to creating a learner-centered environment. The findings suggest that gamification enhances students’ interest, encourages active participation, and improves overall academic performance in English language learning.